Answer:
11/12
Step-by-step explanation:
1/4+2/3
1/4×3/3+2/3×4/4
3/12+8/12
(-4*3*2)^2 = (-24)^2 = 576
hope this will help you
Answer:
(2,-2)
Step-by-step explanation:
The first step is to substitute y in the first equation with the right side of the second equation because they both equal to y.
-3x+4 = 4x-10
-3x-4x+4-4 = 4x-4x-10-4
-7x = -14
-7x/-7 = -14/-7
x = 2
Plugin 2 for x for either equation to solve for y, I'll be using the second equation, but either one is fine.
y = 4(2)-10
y = 8-10
y = -2
Plugin x = 2 and y = -2 into (x,y), and you get (2,-2)
Answer: 2.25 = 18.90
Step-by-step explanation: Hope This Helps
Solving for h means we write the equation in such a way that h is isolated from other variables. It is done as follows:
(P = mgh) 1/mg
P/mg = mgh/mg
h = P/mg
Therefore, the correct answer from the choices listed above is option C, h = p/mg.
Hope this answers the question. Have a nice day.